A meta-narrative review of research traditions on hidden workers in aging population for transdisciplinary implementation research - Sora Lee; Woojin Kang (Frontiers Media S.A., 2024)
Hidden workers are defined as the three vulnerable subgroups of workers: the underemployed, the unemployed, and the discouraged workers. Hidden workers indeed the group with multiple identities; a transitioning retiree, jobseeker, caring for some, who may also have long term health conditions and ethnic minority all at the same time. Designing an intervention for this group necessitates the transdisciplinary knowledge. Transdisciplinary knowledge is crucial because it can inform how the intersectoral challenges might be addressed in interventions, and how the intersectoral implementation design and evaluation on hidden workers might be designed. This paper maps the intellectual landscape of the hidden workers in aging population literature to identify key disciplinary research clusters; and to find out how those research clusters are investigating hidden workers. With the meta-narrative review methodology on studies retrieved from the Web of Science Core Collection, five research clusters were identified: (1) public health approaches to hidden workers, (2) welfare state and aging workforce, (3) older jobseekers, (4) life course perspective, (5) retirement transitions. Each research cluster focuses on different aspects of hidden workers, with varying research questions and rationales. These include conceptualising the determinants of the hidden workers in aging populations and the complex interrelation with public health. Furthermore, we suggest an analytical framework to allow for better understanding between the research traditions based on (1) the chosen socioecological level of analysis, (2) whether the research question is on the determinant for hidden workers or on the outcome of being hidden and (3) the chronosystem (early/middle/later life) timeframe of research question that is addressed. Through this study, we can identify the main issues faced by hidden workers among the older adults and the measures to address these issues as well as opening up a possibility for cross-sectoral policy responses.